Innovation and change management strategies to strengthen the competitive advantage of MSMEs in Bengkulu - Putri, Diesca Adristy Sukma; Kusuma, Adevia Indah (Implementasi Manajemen & Kewirausahaan, 2024)
This study aims to explore innovation and change management strategies as a strategic step to strengthen the competitive advantage of MSMEs in Bengkulu. Using a qualitative descriptive approach, this study analyzes seven indicators of innovation management (including strategic objectives, leadership, collaboration, technology, and organizational learning) and three indicators of change management (technology change, organizational leadership, and culture). The results of the study reveal that the combination of innovation and change strategies significantly increases the flexibility, adaptability, and collaboration of MSMEs in facing market dynamics. These findings provide practical implications in the form of comprehensive guidelines for MSMEs to implement technology, strengthen partnerships, and build a culture of sustainable innovation. The uniqueness of this study lies in its specific focus on MSMEs in Bengkulu, offering new insights into the adaptation of innovation strategies in a dynamic local context.